Efficacy of a Breastfeeding Pain Self-Management Intervention: A Pilot Randomized Controlled Trial. Issue 2 (March 2019) - Lucas, Ruth; Zhang, Yiming; Walsh, Stephen J.; Evans, Heather; Young, Erin; Starkweather, Angela
Abstract : Background: Over 90% of women experience pain during breastfeeding initiation and lack strategies to self-manage breast and nipple pain. Guided by the Individual and Family Self-Management Theory, a breastfeeding self-management (BSM) intervention targeted women's knowledge, beliefs, and social facilitation to manage their breast and nipple pain and achieve their breastfeeding goals. Objectives: The purpose of this longitudinal pilot randomized control trial (RCT) was to test the preliminary efficacy of the BSM intervention on general and specific pain related to breastfeeding. Methods: Sixty women intending to breastfeed were approached within 48 hours of delivery to participate in this pilot RCT (30 randomized to the BSM intervention and 30 randomized to the control group). All participants provided baseline data before discharge and pain and breastfeeding measures at 1, 2, and 6 weeks. Participants in the BSM intervention group received educational modules addressing breast and nipple pain and biweekly, text-based nurse coaching and completed a daily breastfeeding journal. Results: Women in the BSM intervention group reported significantly less breast and nipple pain at 1 and 2 weeks using a visual analog scale ( p < .014 and p < .006) and at 2 weeks using the Brief Pain Inventory intensity scale ( p < .029), but no difference in breastfeeding duration. Discussion: The BSM intervention pilot demonstrates a positive effect on breastfeeding specific and overall generalized pain. Future investigation is needed to identify at-risk women of ongoing breastfeeding pain and develop precision interventions to sustain this beneficial health behavior for mothers and infants. Abstract : Supplemental digital content is available in the text.